MENINGKATKAN KETERAMPILAN BERBICARA DENGAN MENGGUNAKAN ALAT PERAGA SEDERHANA MELALUI DISKUSI KELOMPOK SISWA KELAS II MI NO.39/E.3 JUJUN KABUPATEN KERINCI - Juhendra, Jacki Septia; Guswita, Reni (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
The purpose of this study was to improve speaking skills using simple visual aids through group discussions in class II MI no.39/e.3 Jujun Kerinci district for the 2021/2022 academic year. The research method was class action research, the research subjects were 15 students of class II MI No.39/E/3 Jujun, Kerinci Regency. MI research location No.39/E.2 Jujun, Kerinci Regency. The research procedure consists of the planning stage, the implementation stage, the observation stage and the reflection stage. Data analysis techniques use qualitative and quantitative data. The results of the study illustrate that there is an increase in students' speaking skills by using simple visual aids through a group discussion process given to class II students MI No.39/E/3 Jujun, Kerinci Regency Keywords : Speaking skills, discussion methods